1141 Daytime Napping Trajectory Over Time And Its Association With Cognitive Aging: A 13-year Community-based Longitudinal Study Of Older Adults. (27th May 2020) - Li, P; Gao, L; Gaba, A; Buchman, A S; Bennett, D A; Hu, K; Leng, Y
Abstract: Introduction: Daytime napping is common in elderly adults and has been associated with cognitive impairment. Prior studies have assessed napping at one time point, making it difficult to examine the longitudinal progression of napping and its association with cognitive aging. We examined objectively measured daytime napping longitudinally across different stages of Alzheimer's disease (AD): from no cognitive impairment (NCI), to mild cognitive impairment (MCI), and to Alzheimer's dementia. Methods: We studied 1, 066 participants (female: 810; age: 81.0±7.3 [SD]) in the Rush Memory and Aging Project who have been followed for up to 13 years. Motor activities of up to 10 days were recorded annually and used to assess napping objectively. We defined daytime napping episodes as segments between 10AM and 7PM with continuous zero-activity for ≥10min but <1h (to avoid off-wrist periods). Segments that were <5min apart were merged. Cognitive and clinical evaluations were administered annually to render a clinical diagnostic classification of NCI, MCI, or Alzheimer's dementia. To examine how napping duration and frequency change with the progression of AD, we performed linear mixed-effects models with 2 change points anchored at the diagnoses of MCI and AD while adjusted for age, sex, and education. Results: At baseline, participants had 1.44±0.04 (mean±standard error) naps with an accumulated duration of 35.0±1.1 min per day. Napping duration increased by 5.2±0.3 min and frequency increased by 0.21±0.01 times every year (both p<0.0001). The rate of increase was more than doubled after MCI diagnosis with an annual increase of 11.4±0.7 min in duration and 0.40±0.02 times in frequency (both p<0.0001); these were doubled further after AD diagnosis with an annual change of 26.3±3.1 min in duration and 0.84±0.08 times in frequency (both p<0.0001). Conclusion: Daytime napping duration and frequency increase with aging, and the increase was accelerated with AD progression. Support: This work was supported by NIH grants RF1AG064312, RF1AG059867, R01AG017917, and R01AG56352.